PENGGUNAAN ECONOMIC VALUE ADDED (EVA) UNTUK MENGUKUR KINERJA DAN PENENTUAN STRUKTUR MODAL OPTIMAL PADA PERUSAHAAN TELEKOMUNIKASI (GO PUBLIK) (STUDI KASUS : PT. TELEKOMUNIKASI INDONESIA, TBK DAN PT. INDOSAT, TBK) - AGUSTINA HANAFI; LEONITA PUTRI (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The purpose of this research was to analyze the implementation of Economic Value Added (EVA) as a tool to measure company’s performance based on the financial report at PT. Telekomunikasi Indonesia, Tbk and PT. Indosat, Tbk and also to determine optimal capital structur. The metodh analyze was the financial report of both companies that had been go public The period of measurement of company’s performance was 5 years, from 2007, 2008, 2009, 2010 till 2011. The research finding are. (1) EVA of PT. Telkom, Tbk and PT. Indosat, Tbk during research processes is positive in value and indicated decreasing drastically, which this condition are influenced by NOPAT & WACC. (2) Optimal measurement of capital structure maximal EVA for PT. Telkom, Tbk and PT. Indosat, Tbk in 2007, 2008, and 2009.